Ambiguïté entre technologies propres et meilleures techniques disponibles - Valérie Laforest; Rémi Berthéas (VertigO)
In addition of the cleaner production global objective diffused by the PNUE, two technical approaches coexist : cleaner technologies and best available techniques (BAT). The study of these approaches, notably through French regulation use and voluntary approaches, reveals some ambiguities. In fact, even if they are two preventive strategies, they seem to be different from some aspects we try to clarify in this article. This article begins a though concerning production process environmental approach.